2008
DOI: 10.1007/s11060-008-9736-9
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survival in primary CNS lymphoma treated by high-dose methotrexate monochemotherapy: role of STAT6 activation as prognostic determinant

Abstract: We report a single-center experience of 16 immunocompetent patients diagnosed with primary central nervous system lymphoma and treated with monochemotherapy with high-dose methotrexate (MTX) and deferred radiotherapy. MTX was given at a dose of 8.0 g/m2 for induction and at a dose of 3.5-8.0 g/m2 for maintenance. There were eight complete responses (CR), one partial response, one stable disease, and six patients whose tumors progressed in spite of the chemotherapy. At final follow-up, five of five CRs were ali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 31 publications
2
18
0
Order By: Relevance
“…14 These studies have shown improvement in response rates as compared to HD-MTX alone regimens. 6,[14][15][16] The present study provides additional evidence of this benefit.…”
Section: Discussionsupporting
confidence: 59%
“…14 These studies have shown improvement in response rates as compared to HD-MTX alone regimens. 6,[14][15][16] The present study provides additional evidence of this benefit.…”
Section: Discussionsupporting
confidence: 59%
“…Moreover, another factor that should be considered is that the patients included in this investigation were largely young patients with good performance status. A 50% CR rate with HD-MTX chemotherapy has been reported in a Korean study of PCNSL; 25 thus, ethnicity is possibly another variable that requires evaluation, although there are no available data to support variations in the biology of PCNSL among different ethnicities, yet. As shown in a previous study, HD-MTX/Ara-C was effective in mobilizing hematopoietic stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…Further study with a longer follow-up period would be preferred. However, it could not be easy because of the short survival time of PCNSL patients [3], considering the mean survival time of patients with PCNSL was 33.7 months for a non-ocular group and 32.2 months for an ocular group in a recent study [9].…”
Section: Discussionmentioning
confidence: 99%
“…It usually occurs in elderly or immunodeficient populations, and has increased in incidence during the last several decades [2]. Although the survival rate of patients with PCNSL has recently improved owing to a shift in treatment modality toward methotrexate-based chemotherapy, the median overall survival is still only about 4 years [3][4][5].…”
Section: Introductionmentioning
confidence: 99%